Prevalence of Irritable bowel syndrome among medical students in Erbil city - Rawand Hamza; Sinan Butrus (Advanced Medical Journal)
Background and objectives: Irritable bowel syndrome is a type of functional bowel disease characterized by recurrent abdominal pain associated with a change in stool frequency or consistency without evidence of organic pathology. The objective of this study was to determine the prevalence and risk factors associated with irritable bowel syndrome among medical students in the College of medicine at Hawler medical university.